Nonessential Role for the NLRP1 Inflammasome Complex in a Murine Model of Traumatic Brain Injury - Thomas Brickler; Kisha Gresham; Armand Meza; Sheryl Coutermarsh-Ott; Tere M. Williams; Daniel E. Rothschild; Irving C. Allen; Michelle H. Theus (Hindawi Limited, 2016)
Traumatic brain injury (TBI) elicits the immediate production of proinflammatory cytokines which participate in regulating the immune response. While the mechanisms of adaptive immunity in secondary injury are well characterized, the role of the innate response is unclear. Recently, the NLR inflammasome has been shown to become activated following TBI, causing processing and release of interleukin-1β (IL-1β). The inflammasome is a multiprotein complex consisting of nucleotide-binding domain and leucine-rich repeat containing proteins (NLR), caspase-1, and apoptosis-associated speck-like protein (ASC). ASC is upregulated after TBI and is critical in coupling the proteins during complex formation resulting in IL-1β cleavage. To directly test whether inflammasome activation contributes to acute TBI-induced damage, we assessed IL-1β, IL-18, and IL-6 expression, contusion volume, hippocampal cell death, and motor behavior recovery in Nlrp1−/−, Asc−/−, and wild type mice after moderate controlled cortical impact (CCI) injury. Although IL-1β expression is significantly attenuated in the cortex of Nlrp1−/− and Asc−/− mice following CCI injury, no difference in motor recovery, cell death, or contusion volume is observed compared to wild type. These findings indicate that inflammasome activation does not significantly contribute to acute neural injury in the murine model of moderate CCI injury.